Exploring of occupational risk factors influenced commuting accidents among car drivers - Alias, Ayuni Nabilah; Yaakub, Norwahida; Kujang, Athina Lulong (Faculty of Management Sciences, Yala Rajabhat University, 2024)
The frequency of commuting incidents is increasing every year, and it is becoming a big issue for both organisations and governments. Commuting accidents account for 48% of work-related accidents in Malaysia. However, there are few commuting accidents among manufacturing workers are limited. The aim of this study is to assess the relationship between work characteristics and commuting accidents among respondents. The industrial sector of Kuantan, Pahang was the setting for the cross-sectional study. The population was sampled randomly, and all respondents complied with study inclusion and exclusion criteria. 102 car drivers were selected from various companies in Kuantan. Female frequency is greater than male frequency 40.4% were found in less than 10 kilometres of commuting distance. The significant work factor shows a highly significant correlation between shift work and working schedule towards commuting accidents (r= 0.75, p-value<0.001). This study will be beneficial for other companies to figure out preventive and corrective action to prevent commuting accidents among workers. This study will help other organisations figure out which preventive and corrective measures to take to reduce workplace accidents involving workers' commutes.